A településfejlődés törvényszerűségei - Kőszegfalvi, György (Tér és Társadalom, 1988)
Are there any regularities in the development of the settlements? Similarly identify regularities that, due to their objectivity, are deciding factors in our settlements' development, determine the processes of settlement development, set an objective course – independent of our subjective notions and will – on the basis of which future processes of settlement development can be made probable. Regularities in the development of the settlements–or to be more precise the discovery and studying of these regularities–offer two possibilities. First, a thorough and complex analysis of the past especially recent development may give an opportunity for thinking over, considering and enforcing the lessons of general validity which, in a positive way, by their consequences may contribute to a better balanced development of the settlements. Second, a thorough knowledge of the regularities of the settlement development, the investigation of these regularities and the evaluation of their effects may serve as an opportunity for influencing and guiding the future settlement development attitude more consciously, duly founded and with a scientific demand.